BUDIDAYA, PENGOLAHAN HASIL DAN KELAYAKAN USAHATANI GAMBIR (Uncaria gambir, Roxb.) DI KABUPATEN 50 KOTA - Ermiati Ermiati (Pusat Penelitian dan Pengembangan Perkebunan, 2004)
Cultivation, processing and farming system feasibility of gambier in 50 Kota district, West SumateraGambier (Uncaria gambir Roxb) is one of specific export commodities from west Sumatera. However, this propective cash crop has not followed by the increase of its productivity, quality and farmer income. This conditions, may due to the lack of farmers, know ledge in processing and limited capital for developing gambier farming system. The objective of this research was to evaluate the cultivation and processing techniques, feasibility of farming system, income of gambier farmers and the constrains for developing gambier farming system in this region. The research was conducted in Solok Bio-bio village, Harau sub district, district of 50 Kota, West Sumatera on Januari 2000. The rapid rural iralic (RRI) and survey methodes, by directly dialoque and filling of quistioner were used. Thity respondens were determined by simple random. Farmer income was analyzed 50 by analysis of income, while feasibility of farming system was evaluated by benefit cost ratio (B/C Ratio), net present value (NPV) and internal rate of return (IRR). The results indicated that the cultivation and processing of gambier in this region were still coducted by traditional methods, using simple equipments. The feasibility of farming system showed that at level interest of 15%, the B/C Ratio = 1,61, VPV = Rp. 9.763.532,- and IRR = 57%. Farmer income was Rp. 20.186.250,- or average Rp. 1.682.180,-/year. Based on this results is can be concluded that gambier farming system in Solok Bio-bio was feasible to develop. The main constraints for developing gambier were less of human resources, such as low education, high cost of post harvest, and limited of capital. In order to eleminate these problems emprowering of gambier farmers and its organization, and increasing farmers skill are very urgent.